Overview of Sustainable Urban Planning with Ecologically Friendly Practices - Saha, Biswanath (Journal of Social Science and Humanities, 2025)
This review paper presents an analysis of the pivotal role, that urban planning plays in achieving sustainable development. It explores the complex interplay between urban planning and the pursuit of ecological sustainability. Central to this discussion is the recognition that the way we shape our urban landscapes has profound implications not only for the immediate living conditions of urban residents but also for the long-term health of our planet. Emphasizing sustainability in the realms of urban development reflects an understanding of the intricate links among social, economic, and environmental dimensions. This paper integrates eco-friendly practices to various aspects of sustainable urban planning to illustrate how cities can evolve into more sustainable and livable environments. In this comprehensive analysis, the objective is to underscore the significance of incorporating environmentally friendly approaches into urban planning. This review aims to demonstrate how sustainable practices in urban planning are essential for nurturing a balanced relationship between the growth of urban areas and the preservation of our natural environment.